Answer:
f(x) = (x + 2) (x − 5) (x − 6)
Step-by-step explanation:
f(x) = (x − (-2)) (x − 5) (x − 6)
f(x) = (x + 2) (x − 5) (x − 6)
We know that
If the scalar product of two vectors<span> is zero, both vectors are </span><span>orthogonal
</span><span>A. (-2,5)
</span>(-2,5)*(1,5)-------> -2*1+5*5=23-----------> <span>are not orthogonal
</span><span>B. (10,-2)
</span>(10,-2)*(1,5)-------> 10*1-2*5=0-----------> are orthogonal
<span>C. (-1,-5)
</span>(-1,-5)*(1,5)-------> -1*1-5*5=-26-----------> are not orthogonal
<span>D. (-5,1)
</span>(-5,1)*(1,5)-------> -5*1+1*5=0-----------> are orthogonal
the answer is
B. (10,-2) and D. (-5,1) are orthogonal to (1,5)
Brigitte is shorter than 5 feet. (Brigitte's height=h)
We write this in inequality form
Brigitte's height is h
So 'h' is shorter than 5 feet
Shorter means less than so we use < symbol. We should not use = symbol because height is shorter than 5 not equal to 5.
Suppose if it is given ' height is more than 5 feet ' then we use greater than symbol (>)
h is less than 5 feet
h < 5
Inequality is h < 5
Summaation of a sequence
or see a smaller scale
from 1 to 10
notice
1+10=11
2+9=11
etc
5+6=11
10/2=5
there are 5 pairs
5*11=55
so
1 to 100
1+100=101
2+99=101
...
50+51=101
100/2=50
there ar 50 pairs
50 times 101=5050
the sum is 5050